1984
DOI: 10.1111/j.1469-7610.1984.tb00164.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Illness: Psychosocial Effects on Siblings—i. Chronically Ill Boys

Abstract: Focusing on the adjustment of the siblings of three groups of male children: with pervasive developmental disability, diabetes and no known chronic illness, the present study failed to support the view that siblings of ill children are uniformly at greater risk for psychosocial impairment. However, several domains were identified in which siblings as well as parents of sick children were more susceptible to adjustment problems, though 'risk' seemed to relate more closely to illness-specific variables than the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
80
2
8

Year Published

1990
1990
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(100 citation statements)
references
References 27 publications
10
80
2
8
Order By: Relevance
“…Ferrari [1984] found no differences in behavior problems on the CBCL between siblings ages 6-13 of brothers with PDD, diabetes, and no health or developmental problems. Both Gold [1993] and Kaminsky and Dewey [2002] found no differences in adjustment problems (as measured by the CBCL) between siblings ages 7-18 of children with autism and siblings of TD children (in both studies) and DS [Kaminsky and Dewey, 2002].…”
Section: Sibling Well-beingmentioning
confidence: 86%
See 1 more Smart Citation
“…Ferrari [1984] found no differences in behavior problems on the CBCL between siblings ages 6-13 of brothers with PDD, diabetes, and no health or developmental problems. Both Gold [1993] and Kaminsky and Dewey [2002] found no differences in adjustment problems (as measured by the CBCL) between siblings ages 7-18 of children with autism and siblings of TD children (in both studies) and DS [Kaminsky and Dewey, 2002].…”
Section: Sibling Well-beingmentioning
confidence: 86%
“…Several authors have found that siblings of children with an ASD report positive self-concept similar to norms [Mates, 1990] or comparison groups of siblings of TD children or children with DD or DS [Ferrari, 1984;B€ agenholm and Gillberg, 1991;Rodrige et al, 1993]. Similarly, Verte et al [2003] found that selfconcept did not differ for younger siblings ages 6-11, but that adolescent female siblings age 12-16 of children with high-functioning autism (HFA) had a more positive self-concept than adolescent females of TD siblings.…”
Section: Sibling Well-beingmentioning
confidence: 99%
“…Some studies have reported poor adjustment, higher rates of depression, and poor social competence for siblings of children with autism (Bagenholm & Gillberg, 1991;Gold, 1993). However, other studies have reported siblings of children with autism are typically well-adjusted, with positive self-concepts and good social competence (Ferrari, 1984;Mates, 1990).…”
Section: Introductionmentioning
confidence: 97%
“…Most past studies examining the adjustment of siblings to children with chronic disabilities have been cross-sectional and have not established with certainty whether they are at risk for psychosocial adjustment problems (5)(6)(7). While some studies have used data from fathers (8), siblings (9), or teachers (10,11), mothers have generally been the main respondents (12,13).…”
mentioning
confidence: 99%